Antiferroelectric phase transition in (Sr1-xCax)TiO3: II. X-ray diffraction studies - Ranjan R.; Pandey D. (My University, 2025)
We present here a detailed Rietveld analysis of the structure of paraelectric and antiferroelectric phases of Sr0.70Ca0.30TiO3 using powder XRD data. It is shown that the observed antiferroelectric superlattice reflections can be explained by doubling of the Co parameter of the orthorhombic paraelectric phase. The space groups of the paraelectric (PE) and antiferroelectric (AFE) phases are shown to be Ibnm and Pbcm respectively. The ionic displacements in the antiferroelectric phase reveal that the Ti4+ and Sr2+/Ca2+ ions are displaced in the +[100] direction in a block of three layers followed by their displacements in the -[100] direction in the next block of three layers, leading to the doubling of the cell parameter in the [001] direction. The paraelectric to antiferroelectric phase transition in (Sr0.70Ca0.30)TiO3 and (Sr0.75Ca0.25)TiO3 is shown to be of first order type since (i) the AFE and PE phases coexist around the phase transition temperature and (ii) the lattice parameters change discontinuously at the transition temperature.